Avaliação de metodologias para análise de desempenho de linhas de transmissão frente às descargas atmosféricas - Ronaldo Eugenio de Souza Filho (2013)
The main cause of unplanned outages of transmission lines is related to the effects associated with lightning direct strikes to the line. Furthermore, the rules imposed by the agencies that regulate the electricity sector to the power utility companies are increasingly hard, pursuing a better power quality of the power delivery. Thus, the electrical companies are concerned to meet the requirements of continuity of service. In this context, the lightning performance of transmission lines is an important topic of investigation. The literature presents two consolidated methodologies for the assessment of that performance. These methodologies correspond to formulations developed by the IEEE and CIGRÉ for calculating the number of outages expected in one year for a determined transmission line. This work presents a study of such methodologies and promotes a discussion of the main issues addressed by the methodologies of CIGRÉ and the IEEE to evaluate the lightning performance, specifically in terms of the occurrence of backflashover. Additionally, two relevant topics related to this subject are investigated: the electrical behavior of the transmission line grounding in terms of the representation of the ionization effect and some methods used for representing the disruption process in transmission lines insulators. It is also used a sophisticated methodology for calculating the transmission line outages related to backflashover, which involves the calculation of overvoltages across insulator strings by means of an elaborated computational model (HEM) and the adoption of an established criterion for determining the occurrence of the flashover across insulator strings (DE Model).